Django : the life and music of a Gypsy legend - Dregni, Michael, 1961- (Oxford University Press, 2004)
The first major critical biography of the great jazz musician chronicles the colorful life of guitarist Django Reinhardt, including his long musical relationship with violinist Stephane Grapelli and his wanderings around Europe and the United States.